Good Results in Open Globe Injury Including Intraocular Foreign Body - Widhyasti, Rahayu; Widyanatha, Made Indra; S. Kartasasmita, Arief; Iskandar, Erwin; Virgana, Rova; Ihsan, Grimaldi (Pusat Mata Nasional Rumah Sakit Mata Cicendo Bandung, 2024)
Introduction: The second most frequent cause of open globe injury (OGI) is an intraocular foreign body (IOFB), a serious ocular emergency that needs to be diagnosed and treated right once to avoid blindness. It can enter the eye and cause damage later on, resulting in direct harm. When treating post-traumatic endophthalmitis, an urgent pars plana vitrectomy (PPV) procedure helps maximize visual outcome. Case report: A 55-year-old male patient came to the Emergency Room Tertiary Eye Hospital with chief complaints of blurry vision, pain, and red-eye in his right eye 3 days before admission. The patient’s right eye was hit by a fragment of the sickle knife while mowing the grass in the yard without protective eyeglasses. His chief complaints getting worse accompanied by lacrimation. The patient was diagnosed with Open Globe Injury Type C Grade D Pupil B zone 1, suspected early endophthalmitis, traumatic cataract of the right eye, and hypertension. Pars plana vitrectomy, vitreous tap, antibiotic intravitreal injection (with Ceftazidime and Vancomycin), IOFB extraction, explore, corneal scraping on the wound, cultural resistance, primary hecting of the cornea were done. The visual acuity improved and the infection was resolved. The infection was treated, and visual acuity returned after a month. Conclusion: In ophthalmology, IOFB is one of the most frequent traumas and is regarded as an emergency. To identify this problem, a thorough ophthalmology examination and the relevant ancillary testing should be performed. A patient with good care will have a favorable visual prognosis.